Korelasi Kecanduan Media Sosial Terhadap Motivasi Belajar Mahasiswa Kesehatan UIN Syarif Hidayatullah Jakarta - Tryastuti, Dini; Nurvadillah, Silvi (Universitas Fort De Kock Bukittinggi, 2022)
Background: Learning motivation can be influenced by psychological factors. One that can interfere with psychological health was addiction to social media. This study aims to see the relationship between social media addiction and learning motivation in College students of the Faculty of Health Sciences UIN Syarif Hidayatullah Jakarta. The inclusion criteria in this study were students with the criteria for late teens aged 18-21 years. The instrument used by the researcher were a social media addiction questionnaire and a learning motivation questionnaire. Methods: This research method uses an analytical corelasional research design with a cross sectional approach. Sampling in this study using Stratified Random Sampling technique with a total sample of 296 respondents. This study uses the analysis of the Spearman rank. Results: The results of this study obtained a correlation coefficient of -0.748 and a significance value of 0.000 <0.05. Conclusion: So that this study succeeded in proving the hypothesis which states that there was a strong relationship between social media addiction and learning motivation for students of FIKES UIN Syarif Hidayatullah Jakarta. So that students must be able to use social effectively to avoid the negative impacts of using social media. Keywords: social media, Learning motivation, College Student